2016
DOI: 10.1038/srep23373
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profile of the early stages of breast cancer tumoral spheroids

Abstract: Oxygen or nutrient deprivation of early stage tumoral spheroids can be used to reliably mimic the initial growth of primary and metastatic cancer cells. However, cancer cell growth during the initial stages has not been fully explored using a genome-wide approach. Thus, in the present study, we investigated the transcriptome of breast cancer cells during the initial stages of tumoral growth using RNAseq in a model of Multicellular Tumor Spheroids (MTS). Network analyses showed that a metastatic signature was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Although the literature on this topic is extensive [ 1 7 ], many aspects of tumor cell biology and survival in the context of a 3-dimensional (3D) environment remain poorly understood. For decades the Multicellular Tumor Spheroid (MCTS) model has been used to study clinically relevant aspects of tumor biology, including hypoxia [ 8 ], protein expression patterns within tumors [ 9 11 ], and responses to therapeutics [ 9 , 10 , 12 23 ]. However, relatively few experiments have attempted to use MCTS to further our understanding of tumor cell adaptations within a hypoxic microenvironment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the literature on this topic is extensive [ 1 7 ], many aspects of tumor cell biology and survival in the context of a 3-dimensional (3D) environment remain poorly understood. For decades the Multicellular Tumor Spheroid (MCTS) model has been used to study clinically relevant aspects of tumor biology, including hypoxia [ 8 ], protein expression patterns within tumors [ 9 11 ], and responses to therapeutics [ 9 , 10 , 12 23 ]. However, relatively few experiments have attempted to use MCTS to further our understanding of tumor cell adaptations within a hypoxic microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Spheroids exceeding 400 μm in diameter develop a hypoxic core and activate known survival signaling pathways to maintain cell viability. Tumor cells grown as MCTS, TS, TDTS, and OMS display regional heterogeneity in tumor cell proliferation [ 44 , 46 , 47 ], metabolic activity [ 9 11 , 32 , 44 , 48 , 49 ], and DNA damage repair (DDR) signaling [ 9 , 50 53 ]. In addition to the influence of the 3D microenvironment, the genetic background of the tumor cells and stromal cell populations also contribute to the specifics of spheroid regionalization [ 39 , 54 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coregulation of lncRNAs and neighboring genes is an area of active research in understanding lncRNA functions. For example, 138 coexpressed lncRNA–mRNA pairs were identified from differentially expressed lncRNAs and mRNAs in human glioblastomas [ 74 ] and 63 co-regulated lncRNAs and mRNAs were found in human breast cancer spheroids [ 75 ]. In our study, the overlapping transcripts, HAfT3 and Tex36 (unknown function), and their concurrent increased transcription suggest they may be a linked gene pair for coexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer mammospheres exhibit realistic profiles of oncogenes and tumor biomarkers, which could then be used to identify therapeutic gene targets for metastatic breast cancer 43. A recent study by Pacheco-Marin et al44 found that 3D breast cancer mammospheres displayed a “metastatic signature” involving the downregulation of several cell-adhesion molecules (ie, EPCAM, E-cadherin, integrins, etc), suggesting that the tumor cells were more likely to separate, migrate, and metastasize. Another report has shown that mammospheres express biomarkers (eg, vimentin) that are involved in EMT, which is known to promote tumor metastasis 45.…”
Section: Biological Models For Breast Cancer Researchmentioning
confidence: 99%